Giant coronary artery aneurysm in infantile Kawasaki disease: When to use cardiac computed tomography angiography - Shreeja Kadakia (Clinical Case Reports, 2020)
Abstract Transthoracic echocardiography is the imaging modality of choice for the detection of coronary artery aneurysms (CAAs) in Kawasaki disease. However, cardiac computed tomography angiography is useful in the diagnosis of distal CAAs.